AN UNUSUAL CAUSE OF MALABSORPTION IN AN IMMUNOCOMPETENT HOST - Atul, Sachdev; Ajay, Duseja; Ritambhara, Nada; Harsh, Mohan; Ashish, Bhalla (Journal of Ayub Medical College Abbottabad, 2005)
Gastrointestinal tract infestation with Strongyloides stercoralis is common in the tropical and subtropical areas of the world. In an immunocompetent person, disease is generally asymptomatic. However, it has the potential to cause serious life threatening disease in an immunocompromised patient. We report a 55 years old immunocompetent person who presented with malabsorption secondary to strongyloides stercoralis infestation. Unusual infestations like strongyloides should also be considered while investigating malabsorption. Key words: Malabsorption, Strongyloidiasis, immunocompetent